The effect of pulsatile lavage on antibiotic elution from bone cements in two-stage revision for periprosthetic joint infection - Knappe, Kevin; Schonhoff, Mareike; Bormann, Therese; Nees, Timo A.; Lunz, André; Jäger, Sebastian (Journal of orthopaedic surgery and research, 2025)
Purpose: Periprosthetic joint infection (PJI) is a major complication after total joint replacement, often requiring a two-stage revision with the use of antibiotic-loaded bone cement (ALBC) spacers for local antibiotic therapy. While factors such as cement composition and antibiotic type influence drug release, the impact of pulsatile lavage on antibiotic elution remains unclear. This study investigates the effect of pulsatile saline lavage on the release kinetics of gentamicin and vancomycin from different ALBCs over six weeks. Methods: Three commercially available PMMA bone cements A, B and C were prepared with identical antibiotic concentrations (0.5 g gentamicin, 2 g vancomycin). Rectangular cement blocks were manufactured according to ISO standards. Group A1/B1/C1 (non-lavage) was placed into a buffer solution without further processing. Group A2/B2/C2 (lavage) was treated with a defined amount of saline solution using high-pressure pulsatile saline lavage before being placed into the buffer solution. Antibiotic release was analyzed at ten predefined time points (T) over six weeks (5 h, 1 d, 2 d, 4 d, 1/2/3/4/5/6 weeks). All samples were stored in an incubator at 36 °C. Results: Statistically significant differences in the release kinetics of both gentamicin and vancomycin were observed for bone cement A and B after processing with saline lavage. Gentamicin release differed significantly between A1/A2 at T2 and T7–T10, and between B1/B2 at T1, T7, and T10; no significant differences were found between C1/C2. Cumulatively, only B1 vs. B2 showed a significant difference in gentamicin release (p = 0.033). Vancomycin release differed significantly between A1/A2 at T1 and T5–T9, and between B1/B2 at T6; again, no significant differences were seen in C1/C2. Cumulative vancomycin release was significantly reduced in B2 compared to B1 (p < 0.001). In four of six cements, vancomycin release declined by over 85% from T1 (5 h) to T3 (48 h). Conclusion: Pulsatile high-pressure lavage is an essential part of revision surgery due to its mechanical cleansing effects. However, this study indicates that its impact on antibiotic release from loaded bone cement is minimal. While variations exist depending on cement type, lavage does not seem to substantially alter the elution profile or expected antimicrobial efficacy.